Synthesis, SAR and biological evaluation of a novel series of 1-(2-chloroethyl)-1-nitroso-3-(2-(3-oxobenzoelenazol-2(3H)-yl)ethyl) urea: Organoselenium compounds for cancer therapy - Ye, S; Zheng, X; Hu, T; Zeng, H (Cellular and Molecular Biology, 2016)
Thioredoxin reductase 1 (TrxR1) is an important potential anticancer drug target and closely related to both carcinogenesis and cancer progression. Ethaselen (BBSKE), a novel organoselenium compound inhibiting TrxR1 with selective antitumor effect, while its symmetrical structure results in poor solubility. Carmustine (BCNU), a DNA cross-link agent and also a deactivator of TrxR, is with high toxicity and low selectivity which limit its clinical application to some extents. Herein, a novel compound, 1-(2-chloroethyl)-1-nitroso-3-(2-(3-oxobenzoelenazol-2(3H)-yl)ethyl)urea(4a-1), which was designed through the combination of Ethaselen and Carmustine, showed good solubility, good tagetability, low toxicity and excellent antitumor activity by synergism. Using the structure of 4a-1 as a key active scaffold, a series of novel 1-(2-chloroethyl)-1-nitroso-3-(2-(3-oxobenzoelenazol-2(3H)-yl)ethyl)urea was designed, synthesized and evaluated to explore the structure-activity relationships (SARs) of these inhibitors and to improve their antitumor activities. Notably, 1-(2-chloroethyl)-3-(2-(6-fluoro-3-oxobenzoselenazol-2(3H)-yl)ethyl)-1-nitrosourea(4b-1) was found to exhibit more potent antitumor activities comparable to 4a-1 against all the four cancer cell lines, including Mia PaCa-2, PANC-1, RKO, LoVo. These results have highlighted compound 4b-1 as a new potential lead candidate for future development of novel potent broad-spectrum antitumor agents. In addition, a SAR model was established to conduct further structural modification.